SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LOKASI SPBU MENGGUNAKAN MOOSRA - Harefa, Sinema; Sihombing, Volvo; Juledi, Angga Putra (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
This study aims to develop a decision support system (DSS) based on the Multi-Objective Optimization on the basis of Simple Ratio Analysis (MOOSRA) method in determining the optimal location of Public Fuel Filling Stations (SPBU) in Kubu District, Rokan Hilir, Riau. The main issue faced is the selection of SPBU locations involving various criteria such as accessibility, population density, level of competition, potential for economic growth, and supporting facilities. The MOOSRA method was chosen because of its ability to manage various criteria objectively and systematically. In this study, an analysis of several alternative SPBU locations and calculations using a normalized matrix were carried out to produce location rankings. The results showed that the best alternative location was A3 with the highest ranking, followed by A4 and A1. By implementing MOOSRA-based DSS, the process of selecting SPBU locations in Kubu District, Rokan Hilir, Riau becomes more efficient and objective.